How Do College Students with Disabilities Do? Law, Self-determination, Self-advocacy, and Campus Resources - Jeong IL Cho; Kate Jones (Journal of the Scholarship of Teaching and Learning, 2024)
Abstract: This survey study investigated understanding and use of the Americans with Disabilities Act (ADA), self-advocacy, self-determination, and campus resources by college students with disabilities. Thirty-one students registered with a student disability office at a Midwestern state university completed an anonymous survey. Thirty-two percent of participants reported that they knew how to advocate for their own education before beginning college. A majority of participants displayed strong understanding of self-determination, self-advocacy, and campus resources, but reported a weak understanding about the ADA. Participants reported stronger agreement on their use of self-determination and self-advocacy skills than on campus resources. Their lowest score was for their use of self-advocacy skill when their legal rights had to be voiced. These students’ lack of understanding of their legal rights and limited self-advocacy skills in protecting their legal rights suggest implications for both transition services in high school and support services at the college level.